Facile synthesis of WOx/ZrO2 catalysts using WO3·H2O precipitate as synthetic precursor of active tungsten species. (December 2020) - Piva, D.H.; Piva, R.H.; Pereira, C.A.; Silva, D.S.A.; Montedo, O.R.K.; Morelli, M.R.; Urquieta-González, E.A.
Abstract: Zirconia-supported tungsten oxide (WOx /ZrO2 ) catalysts were successfully synthesized using a suspension containing amorphous hydrous zirconia precipitates [ZrOx (OH)4-2x ·yH2 O]n and tungstate monohydrate (WO3 ·H2 O) precipitates. The procedure involved the dissolution of the WO3 ·H2 O precipitate during the aging process with the release of oxyanion [WO4 ] 2- species, interaction of this species with the surface of the [ZrOx (OH)4-2x ·yH2 O]n precipitate and, formation of active WOx species after thermal treatment. Non-bridging hydroxyl (OH − ) groups present in the [ZrOx (OH)4-2x ·yH2 O]n precipitate act as an active agent for the WO3 ·H2 O dissolution. N2 physisorption, X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), temperature-programmed reduction using hydrogen (H2 -TPR), temperature-programmed desorption of ammonia (NH3 -TPD), Fourier-transform infrared (FTIR) spectroscopy of adsorbed pyridine, and Raman spectroscopy were used to elucidate the catalyst structure–performance relationship. The catalytic activity was evaluated for the oxidative desulfurization (ODS) of a model fuel containing dibenzothiophene (DBT). For a fixed WO3 ·H2 O content, longer aging times improved the catalyst activity, reaching a maximum when WO3 ·H2 O was completely dissolved. The increase in surface area and formation of more active Zr-WOx clusters and polytungstates are observed for the highest active catalysts. A synergetic effect between local Lewis and Brønsted acid sites seems to have contributed to the observed superior activity. The proposed strategy provides an efficient approach to produce active WOx /ZrO2 catalysts and may be applicable for designing other heterogeneous catalytic systems. Graphical abstract: Image 1 Highlights: WOx /ZrO2 catalysts were prepared from a novel synthesis route. [ZrOx (OH)4-2x ·yH2 O]n and WO3 ·H2 O precipitates as precursors of the support and WOx species. WO3 ·H2 O dissolution by aging generated [WO4 ] 2- species interacting with the [ZrOx (OH)4-2x ·yH2 O]n surface. [WO4 ] 2- oxyanions promoted formation of more actives Zr-WOx clusters and polytungstates species. Synthesized WOx /ZrO2 catalysts were highly active to ODS of a model fuel containing DBT.